2010
DOI: 10.1007/s00381-010-1204-0
|View full text |Cite
|
Sign up to set email alerts
|

Extended endoscopic endonasal approach to the suprasellar parachiasmatic cisterns: anatomic study

Abstract: The EEASR, a minimally invasive route to suprasellar parachiasmatic area, provided wide exposure of the basal cisterns. The surgical areas that were accessed through the subchiasmatic corridor could be divided into a medial part that included the interpeduncular and prepontine cisterns and a lateral part that contained carotid and sylvian cisterns superiorly and the crural and ambient cisterns inferiorly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…If nasal pack for controlling severe epistaxis leads to pain and extreme discomfort and if nasal obstruction, dysphagia and occlusion of auditory tube are present and no response can be obtained from medication and pack therapy, arterial ligation is applied (Abelson et al; Maceri). Transanthral, transoral or endonasal endoscopic intervention methods are used for ligating the 3rd part of the maxillary artery and sphenopalatine artery (Stepnick et al, 1990;Abelson et al;Maceri;Voegels et al, 2001;Schwartzbauer et al;Kumar et al, 2003;Pradess et al, 2008;Abuzayed et al). Arterial embolization is used as an alternative and efficient method for persistent posterior epistaxis cases and it is performed under angiographic guidance (Maceri).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If nasal pack for controlling severe epistaxis leads to pain and extreme discomfort and if nasal obstruction, dysphagia and occlusion of auditory tube are present and no response can be obtained from medication and pack therapy, arterial ligation is applied (Abelson et al; Maceri). Transanthral, transoral or endonasal endoscopic intervention methods are used for ligating the 3rd part of the maxillary artery and sphenopalatine artery (Stepnick et al, 1990;Abelson et al;Maceri;Voegels et al, 2001;Schwartzbauer et al;Kumar et al, 2003;Pradess et al, 2008;Abuzayed et al). Arterial embolization is used as an alternative and efficient method for persistent posterior epistaxis cases and it is performed under angiographic guidance (Maceri).…”
Section: Discussionmentioning
confidence: 99%
“…Although course and parts of the maxillary artery are defined in classical anatomy books, significant clinical information related with the main artery and its branches are included in several investigation reports (Navarro et al, 1982;Morton & Khan, 1991;Vrionis et al, 1996;Sashi et al, 1996;Choi & Park, 2003;Schwartzbauer et al, 2003;Isolan et al, 2007;Hussain et al, 2008;Abuzayed et al, 2009;Chiu, 2009;Kwak et al, 2010). As the most important contribution to the blood supply of the nose is made by maxillary artery from the external carotid system, it is reported that ligation of the maxillary artery and its branches via different procedures is the most efficient method for controlling the epistaxis (Stepnick et al, 1990;Abelson, 1991;Maceri, 1993;Abuzayed et al, 2009;Kwak et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, even though in some studies an endoscopic endonasal route above the chiasm has been suggested, we considered this approach to be a major risk for visual chiasm or nerve damage. 1 Therefore, careful analysis of high-resolution preoperative imaging studies is of paramount importance before this route is considered.…”
Section: Discussionmentioning
confidence: 99%
“…In general, vessels from the overlying pial network supply the chiasm. Inferiorly, the largest vessel contributing to this network is the superior hypophyseal artery, which gives off a recurrent branch along the inferomedial border of the proximal intracranial part of the optic nerve (Blunt and Steele, 1956;Abuzayed et al, 2010). These paired vessels are routinely encountered adherent to the tumor capsule in the endonasal endoscopic removal of VISUAL LOSS communicating arteries.…”
Section: Visual Lossmentioning
confidence: 97%